2017
DOI: 10.3389/fneur.2017.00384
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Improvement and Brain Changes after Real-Time Functional MRI Neurofeedback Training in Healthy Elderly and Prodromal Alzheimer’s Disease

Abstract: BackgroundCognitive decline is characteristic for Alzheimer’s disease (AD) and also for healthy ageing. As a proof-of-concept study, we examined whether this decline can be counteracted using real-time fMRI neurofeedback training. Visuospatial memory and the parahippocampal gyrus (PHG) were targeted.MethodsSixteen healthy elderly subjects (mean age 63.5 years, SD = 6.663) and 10 patients with prodromal AD (mean age 66.2 years, SD = 8.930) completed the experiment. Four additional healthy subjects formed a sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 83 publications
4
51
0
Order By: Relevance
“…The ability for one rt-fMRI neurofeedback session to make lasting changes to neural processes and symptomology is less credible. Limited work suggests that patients with schizophrenia benefited from two sessions of neurofeedback, and that a third did not add to their ability to regulate (Dyck et al, 2016), but Hohenfeld et al (2017) found that older adults didn't improve in their ability to regulate after the first session. Neither of these studies were designed to evaluate the influence of number of sessions on sustained behavior or symptom changes at follow-up.…”
Section: Recommendationmentioning
confidence: 96%
See 1 more Smart Citation
“…The ability for one rt-fMRI neurofeedback session to make lasting changes to neural processes and symptomology is less credible. Limited work suggests that patients with schizophrenia benefited from two sessions of neurofeedback, and that a third did not add to their ability to regulate (Dyck et al, 2016), but Hohenfeld et al (2017) found that older adults didn't improve in their ability to regulate after the first session. Neither of these studies were designed to evaluate the influence of number of sessions on sustained behavior or symptom changes at follow-up.…”
Section: Recommendationmentioning
confidence: 96%
“…The ability to regulate activity associated with cognition with the aid of rt-fMRI neurofeedback have also been investigated, with 12 published studies using various tasks. Individuals are able to use neurofeedback to improve sustained attention (Debettencourt et al, 2015), working memory (Zhang et al, 2013), and visual memory (Hohenfeld et al, 2017). There may also be potential to use this technique in prodromal stages of Alzheimer's, individuals with schizophrenia (Cordes et al, 2015), adults with ADHD (Zilverstand et al, 2017), and major depressive disorder (Schnyer et al, 2015).…”
Section: Behavioral Domains Where Neurofeedback Has Been Investigatedmentioning
confidence: 99%
“…Another study demonstrated that neurofeedback participants could regulate the DLPFC and improve working memory performance compared to a mental rehearsal control . In a more recent study, participants failed to regulate their parahippocampal gyrus, but improved on 3 of 14 memory tests (Hohenfeld et al, 2017); however, the researchers make no mention of accounting for multiple comparison and they used an underpowered placebo-nf group with four participants, compared to the 16 receiving genuine-nf.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Biofeedback of real-time functional magnetic resonance imaging data from t SMA supplementary motor area Hanlon et al, (2013) . Reduction of cue-induced craving through realtime neurofeedback in nicotine use PMC premotor cortex Harmelech et al, (2015) Hohenfeld, C., Nellessen, N., Dogan, I., Kuhn, H., Müller, C., Papa, F., et al (2017). Cognitive improvement and brain changes after real-time functional MRI neurofeedback PHC parahippocampal cortex Hui et al, (2014); Xie et al, Karch, S., Keeser, D., Hümmer, S., Paolini, M., Kirsch, V., Karali, T., et al (2015).…”
Section: Fcmentioning
confidence: 99%
“…In the first study of its kind, applying an integrated IEEG-fMRI method, we have shown that established markers of memory encoding correspond to meaningful network differences captured by rsfMRI. In clinical terms, knowing a region is a hub, playing an important role in multi-regional and multi-functional connectivity, may inform technologies trying to identify the most effective targets to electrically or pharmacologically stimulate for cognitive enhancement in areas such as memory Ezzyat Y et al, 2018;Kucewicz MT et al, 2018), or perhaps be used to identify the areas with sufficient influence over targets to generate effective neuro-feedback loops (Hohenfeld C et al, 2017;Murphy AC et al, 2017).…”
Section: Discussionmentioning
confidence: 99%